Towards validated MHD modeling of edge harmonic oscillation in DIII-D QH-mode discharges. (22nd July 2020) - Pankin, A.Y.; King, J.R.; Kruger, S.E.; Chen, Xi; Burrell, K.H.; Garofalo, A.M.; Groebner, R. J.; McKee, G.R.; Yan, Z.
Abstract: The extended-MHD NIMROD code (Sovinec C.R. and King J.R. 2010 J. Comput. Phys. 229 5803) is used to simulate the dynamics of an edge harmonic oscillation (EHO) in quiescent H-mode (QH-mode) DIII-D (Luxon J.L. 2002 Nucl. Fusion 42 614) discharge 163 518. EHOs observed in non-linear MHD simulations have n  = 1 and n  = 2 as dominant modes akin the DIII-D experiment. Kinetic equilibrium reconstructions during the time of the fully-developed EHO include the effect of the MHD profile relaxation and are found below the stability boundary. This paper discusses methods to include additional instability drives to the experimental equilibria in order to trigger EHO formation. The experimental equilibrium for the DIII-D discharge 163 518 is modified to include two levels of instability drive by increasing the experimental pressure gradient. In order to do a more direct comparison of the simulation results with the experiment, a synthetic BES diagnostic is used to compute cross-correlation and cross-power spectral densities associated with the simulated density perturbations. It is shown that the amplitude of the experimental density perturbations is between the computed density perturbation amplitude for the two levels of instability drive. The synthetic cross-power spectral density shows a transition from a double to a single peak in frequency when the BES analysis shifts from near the LCFS towards the steep gradient region of the pedestal. This observation is similar to the experiment, but the first peak frequency for the weak instability drive is found below the experimental frequencies, and the second peak for the strong instability drive is found above the experimental peak frequencies. However, these peak frequencies are in agreement with the local flow estimate and a MHD turbulence bursty behavior in the simulations with the strong instability drive.